Comparison of volumetric analysis between conventional and rotary files in the preparation of root canals in primary molars—an in vitro study - Vishwanathaiah, Satish (Frontiers in Dental Medicine, 2024)
BackgroundTo compare and evaluate the efficacy of canal preparation and volumetric filling of primary molars instrumented by conventional hand K-file, ProAF baby rotary file and Kedo-S square file using cone beam computed tomography.Materials and methodsThirty freshly extracted human primary second molars were randomly divided into 3 groups of 10 teeth each. After access opening and working length determination, preoperative volume analysis was done using cone beam computed tomography (CBCT). The canals were then instrumented by either hand K-files, Pro AF Baby rotary files and Kedo-S square rotary files. Post operative volume analysis was performed using CBCT. All the canals were obturated using Metapex and scanned again using CBCT. Mean values of the pre- and post-operative canal volumes were analyzed using one-way ANOVA. Inter- and intra- group volumetric changes were analyzed statistically by post hoc test.ResultsThe mean difference in volume after canal preparation and obturation was the highest in the hand K-file group, followed by Pro AF Baby Gold group and the least in the Kedo-S square group. Inter and intra group comparison showed statistically significant differences for all the file groups used.ConclusionKedo- S square showed the least difference in preparation volume and better obturating volume compared to Pro AF baby gold file systems.